DRAINAGE SYSTEM DESIGN INTERNATIONAL AIRPORT SYAMSUDIN NOOR - Ahmad Fadhillah; M. Azhari Noor; Maya Amalia (CERUCUK, 2017)
Location studies Syamsudin Noor city is located in the city Banjarbaru, South Kalimantan. Poor drainage systems can cause waterlogging that may interfere with the function of airports. Is devoted to the planning of drainage channels to avoid puddles on the runway (runway).Rainfall data is processed by analyzing the frequency, which is the chosen distribution Log Pearson III. After it was made curved rainfall intensity using rational formula for some period of 5 years return period. Analyses were performed per Segmentst adjusted with drainage coefficient of each Segmentst to obtain a discharge plan.After analyzing the obtained Qmaks worth 5,101 m3 / s, the existing drainage channel is still able to accommodate the discharge plan. Then do the economic planning of drainage channels, obtained H = 1.4m and B = 1m for trunking and H = 0.8 m and B = 0.7m for the trapezoidal channel.Keywords: Syamsudin Noor Airport, runway, drainage